2010
DOI: 10.1111/j.1365-2869.2010.00904.x
|View full text |Cite
|
Sign up to set email alerts
|

Sudden early-morning awakening impairs immediate tactical planning in a changing ‘emergency’ scenario

Abstract: Summary This was a realistic military‐type exercise assessing unexpected, abrupt early‐morning awakening effects on immediate ‘executive function’ and the ability to comprehend and deal with a sudden emergency under a changing situation. Twenty (average age 21 years) healthy, highly motivated junior officer reservists were assigned randomly to two equal, independent groups, unforewarned as to what would happen. The experimental group was woken abruptly at 03 : 00 h (<3 h sleep) and confronted immediately with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 20 publications
(41 reference statements)
1
34
0
1
Order By: Relevance
“…Military personnel are often subjected to SD during combat operations or peacekeeping missions abroad [5][6][7]. Frequent SD of these military personnel could, conceivably, affect brain function and reduce their ability to perform at optimal levels [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Military personnel are often subjected to SD during combat operations or peacekeeping missions abroad [5][6][7]. Frequent SD of these military personnel could, conceivably, affect brain function and reduce their ability to perform at optimal levels [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive control components of executive function are critical for modulation of other cognitive processes, such as looking in the correct direction when crossing the street while visiting a country where people drive on a different side of the road, or inhibition of inappropriate outbursts and behaviours in patients with dementia. Our findings may also have important implications for the millions of individuals working at adverse circadian phases, long working hours and/or immediately upon awaking (Horne and Moseley, 2011), including health-care professionals treating patients, with the acknowledgement that findings from laboratory studies may not translate directly to real world performance. Lastly, our findings highlight the importance of considering how sleep inertia, hours awake and circadian processes may influence clinical assessments of cognitive impairment.…”
Section: Discussionmentioning
confidence: 96%
“…Groeger et al (2011) have also shown working memory executive function to be influenced by sleep inertia following afternoon naps. Additional research is necessary to determine if other executive functions (Alvarez and Emory, 2006) are influenced primarily by circadian phase and test such executive functions under real world conditions (Horne and Moseley, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The intensity and duration of sleep inertia vary based on situational factors, but its effects may last minutes to several hours. Sleep inertia is a normal phenomenon, but one with potentially dangerous ramifications, e.g., in health care workers or military personnel who are woken abruptly in the night and required to make cognitively-taxing decisions [1, 2]. In some disease states, a transitional period akin to markedly pronounced sleep inertia is present and is sometimes referred to as “sleep drunkenness”.…”
Section: Introductionmentioning
confidence: 99%